Operationalising AI Regulatory Sandboxes under the EU AI Act: The Triple Challenge of Capacity, Coordination and Attractiveness to Providers - Ahern, Deirdre (My University, 2025)
The EU AI Act adopted in 2024 provides a rulebook for all AI systems being put on the market or into service in the European Union. This article investigates the AI Act’s requirement that Member States establish national AI regulatory sandboxes for testing and validation of innovative AI systems under regulatory supervision to assist with fostering innovation and complying with the Act’s regulatory requirements. Regulatory sandboxes are well-diffused around the globe for fintech, but the AI Act presents a new and unique setting given the broad swathe of risks it covers from health and safety to ethics and fundamental rights. Against the backdrop of the EU’s objective that AI regulatory sandboxes would both foster innovation and assist with compliance, considerable challenges are identified for Member States around capacity-building and design of regulatory sandboxes. While Member States are early movers in laying the ground for national AI regulatory sandboxes, the article contends that there is a risk that differing approaches being taken by individual national sandboxes could jeopardise a uniform interpretation of the AI Act and its application in practice. This could motivate innovators to play sandbox arbitrage. The article therefore argues that the European Commission and the AI Board need to act decisively in developing rules and guidance to ensure a cohesive, coordinated approach in national AI regulatory sandboxes. With sandbox participation being voluntary, the possibility that AI regulatory sandboxes may prove unattractive to innovators on their compliance journey is also explored. Confidentiality concerns, the inability to relax legal rules during the sandbox, and the inability of sandbox’s to deliver a presumption of conformity with the AI Act are identified as pertinent concerns for innovators contemplating applying to AI regulatory sandboxes as compared with other direct compliance routes provided to them through application of harmonised standards and conformity assessment procedures.
IN_PRESS
Keywords: AI regulation; EU AI Act; AI regulatory sandboxes; regulatory sandboxes; experimental regulation; Regulating technologies; Artificial Intelligence; Computers and Society; European Union Law; Digital Engagement; International Integration; Smart & Sustainable Planet; EU Law; law and technology